2001
DOI: 10.1177/104973150101100603
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive-Behavioral Therapy of Grief: A Review and Application

Abstract: This article reviews outcome studies of grief therapy, with special attention to the cognitive perspective. Based on those studies, three observations on bereavement interventions are offered: (a) development of psychotherapy interventions has been strongly linked to theoretical conceptualizations and definitions of what constitutes normal, pathological, and chronic grief at different times after bereavement; (b) in most reported studies, generic non-bereavement scales were applied for measuring reduction of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(25 citation statements)
references
References 38 publications
(65 reference statements)
1
21
0
2
Order By: Relevance
“…The literature review confirmed that adolescents experience a range of physical, emotional, social and cognitive responses related to their perinatal loss (Bright 1987;Malkinson 2001;Welch and Bergen 1999;Wheeler 1997;Wheeler andAustin 2000, 2001). Upon review of the 25 perinatal loss cases suggest that adolescents typically fell into three categories: The grieving adolescent who acknowledges the loss of her baby.…”
Section: Anticipatory Guidance Related To the Meaning And Impact Of Lossmentioning
confidence: 70%
See 2 more Smart Citations
“…The literature review confirmed that adolescents experience a range of physical, emotional, social and cognitive responses related to their perinatal loss (Bright 1987;Malkinson 2001;Welch and Bergen 1999;Wheeler 1997;Wheeler andAustin 2000, 2001). Upon review of the 25 perinatal loss cases suggest that adolescents typically fell into three categories: The grieving adolescent who acknowledges the loss of her baby.…”
Section: Anticipatory Guidance Related To the Meaning And Impact Of Lossmentioning
confidence: 70%
“…Rando's (1986) grief phases in bereaved older adults appears applicable to adolescents, however, it does not recognize the last category; the adolescent who does not acknowledge a loss. In addition, all the literature review (Barglow et al 1973;Bright 1987;Horowitz 1978;Malkinson 2001;Smith et al 1984;Welch and Bergen 1999;Wheeler 1997;Wheeler andAustin 2000, 2001) acknowledged that adolescents resembled a mourning process. Horowitz (1978) concluded that adolescents with few grief responses felt this way due to lack of emotional or social support.…”
Section: Anticipatory Guidance Related To the Meaning And Impact Of Lossmentioning
confidence: 95%
See 1 more Smart Citation
“…Some have conceptualized bereavement as an event to which individuals respond via these cognitive processes (e.g., Dyregrov and Matthiesen 1987;Horowitz et al 1981). More general cognitive-behavioral perspectives have also been applied to the grief experience (e.g., Boelen et al 2006;Gluhoski 1995;Malkinson 2001). Irrespective of its theoretical stance, grief research is typically orientated around separating normal from pathological grief, identifying determinants of individual variability in grieving, identifying grief outcomes, and examining the efficacy and effectiveness of grief interventions (Bonanno and Kaltman 1999; Centre for the Advancement of Health 2004).…”
Section: Introductionmentioning
confidence: 99%
“…These memories usually revolve around traumatic events that are emotionally painful. Reliving such affective experiences may be beneficial to a point, as in bereavement [24]. However, lacking control over such memories may allow them to repeatedly become intrusive and ruminative in nature.…”
Section: Introductionmentioning
confidence: 99%